A Analisis Pewarna Rhodamin B dan Pengawet Asam Benzoat dalam Saus Tomat di Kota Banjarmasin - tuti alawiyah; Rahmadani Rahmadani (Jurnal Pelayanan Kefarmasian dan Sains, 2021)
Background: Tomato sauce with a red color is often misused by manufacturers by adding coloring agents that are prohibited for use in food such as Rhodamin B. Tomato sauce is also usually made by adding preservatives such as Benzoic Acid which cannot be dissociated, causing toxic effects on excessive use. Objective: to analyze the coloring ingredients and preservatives in terms of qualitative analysis and quantitative analysis in several tomato sauce products circulating in Banjarmasin City. Methods: the research method is analytical description by identifying rhodamine b compounds using Thin Layer Chromatography and UV-VIS Spectrophotometry with a wavelength of 534 nm in samples of ketchup A and B, then identification of Benzoic Acid compounds is carried out by qualitative analysis, namely color test with FeCl3 reagent, acid-base titration and UV-VIS spectrophotometric method with a wavelength of 230 nm. Results: solvent KLT method used by using butanol: ethyl acetate: ammonia solvent with a ratio of 10:4:5) The results showed that the Rf value for sample 1 and sample 2 was 0.9966 cm. The results of quantitative analysis of rhodami b using UV-VIS spectrophotometer method with a wavelength of 543 nm Regression calibration curve obtained line equation y = 0.02265 x + 0.0226 with a correlation coefficient (r) of 0.998330, average sample 5.371. Conclusion: The identification results of Rhodamin B do not meet the requirements of the Permenkes, while the results of benzoic acid still meet the SNI standards.